BETWEEN POWER AND COOPERATION: A REALISM-LIBERALISM STUDY OF INDONESIA'S BRICS MEMBERSHIP IN A MULTIPOLAR WORLD - Firman Prima Laras (Universitas Budi Luhur, 2025)
Abstract: This study analyzes the dynamics of discourse, motivations, and Indonesia's decision to join BRICS, using the lenses of realism and liberalism in international relations.The realist perspective views Indonesia’s move as an effort to strengthen its bargaining position amid great power rivalries, diversify export markets, and secure strategic resources, as reflected in the dominance of non-oil and gas exports to China and India based on BPS 2023 data. The liberal perspective emphasizes the opportunities to expand multilateral cooperation, promote South-South solidarity, and access development financing through the New Development Bank. This research employs a qualitative document-based method, triangulating trade data, official government statements, media reports, and international relations literature (Kaufman, 2022; Stuenkel, 2020; Kauppi & Viotti, 2020; Nau, 2019). The findings indicate that Indonesia integrates both realist and liberal approaches in considering its BRICS membership: realist power calculations are manifested through strategic partner diversification, while liberal aspirations are reflected in the commitment to strengthening Global South cooperation. Indonesia’s decision to join BRICS reflects a cautious strategic approach, weighing economic-political benefits while upholding the